2020
DOI: 10.31234/osf.io/r54ec
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in Respondent Speed and its Implications: Evidence from an Adaptive Testing Scenario

Abstract: As our ability to collect data about respondents increases, approaches for incorporating ancillary data features such as response time are of heightened interest. Models for response time have been advanced, but relatively limited large-scale empirical investigations have been conducted. We take advantage of a unique and massive dataset—data from computer adaptive administrations of the NWEA MAP Growth assessment in two states consisting of roughly 1/4 billion item responses—containing both item responses plus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Other features of data collection may be relevant. We have not addressed ordering effects (Debeer & Janssen, 2013; Domingue et al, 2021; Vida et al, 2021). There are presumably motivational differences across the data sets that we do not measure and cannot study.…”
Section: Discussionmentioning
confidence: 99%
“…Other features of data collection may be relevant. We have not addressed ordering effects (Debeer & Janssen, 2013; Domingue et al, 2021; Vida et al, 2021). There are presumably motivational differences across the data sets that we do not measure and cannot study.…”
Section: Discussionmentioning
confidence: 99%
“…The approach used here-in particular, combining 206 probabilities from item response models with fixed 207 effects-draws from earlier work [19]. 3 We have also 208 verified that it behaves as expected via simulation in 209 the context of several different models for the joint 210 distribution of time and accuracy, see SI.…”
mentioning
confidence: 55%
“…In many cases, items later in the test may appear harder than they would if presented earlier in the test. This may be due, in part, to systematic changes in response time devoted to such items [19].…”
mentioning
confidence: 99%
“…Prior research has shown that examinees with lower ability are more likely to engage in RG, particularly as a test progresses (e.g., Deribo et al, 2021; Domingue et al, 2021; Rios et al, 2017). To investigate the influence of this factor, two conditions were manipulated to reflect differences in the ability characteristics of rapid guessers.…”
Section: Methodsmentioning
confidence: 99%
“…3This RG generating process also reflects response acceleration (i.e., response time reduction for later responses provided in a test) observed in prior applied analyses (Domingue et al, 2021). …”
mentioning
confidence: 92%